Programmed cell death in procyclic Trypanosoma brucei rhodesiense is associated with differential expression of mRNAs - Murphy, N.B.; Welburn, S.C. (1997)
Procyclic Trypanosoma brucei rhodesiense have a cell death mechanism which can be activated by an external signal, the lectin ConA, in vitro. ConA has been shown to cause profound changes in cellular morphology and induce fragmentation of nuclear DNA in T.b. rhodesiense which are characteristic of apoptosis, a form of programmed cell death (PCD) in other eukaryotic cells. RNA analysis of trypanosomes induced to undergo PCD revealed that RNA remains intact up to 48 h into the process, a time when nuclear DNA fragmentation has already started. Using the randomly amplified differentially expressed sequences polymerase chain reaction method, ConA-induced cell death in T.b rhodesiense is shown to be associated with differential expression of mRNAs, including up regulation of mRNAs late in the death process. The results demonstrate that trypanosomes actively participate in their own destruction through a PCD process and confirm that cell death in trypanosomes is associated with de novo gene expression.